Development, validation and reliability of knowledge, attitudes and practice questionnaire for people affected by leprosy reactions - Asiyah T. Maulana; Annisa Ika Putri; Brittney S. Mengistu; Stephen L. Walker; Ruth M. H. Peters (Global Public Health)
Leprosy reactions occur in 20–50% of people affected by leprosy. Previous studies have shown that lack of awareness and understanding of leprosy reactions among affected individuals and healthcare workers. This study aims to design and validate a knowledge, attitudes, and practices (KAP) questionnaire to assess understanding of leprosy reactions among leprosy-affected individuals. This study employed a sequential exploratory design in three phases. During interviews, affected individuals expressed dissatisfaction with the level of information provided by medical practitioners regarding leprosy reactions. People affected by leprosy reactions shared experiences of frustration, treatment barriers, and difficulties with daily activities during interviews and workshops. The pilot test with eight affected individuals let to the removal of one question, the addition of a new question, and adjustment to wording and instructions. Cronbach’s alpha was calculated based on data collected from 63 individuals. The overall Cronbach’s alpha was 0.71. The final KAP questionnaire consists of 39 questions, is considered clear and acceptable by users and can therefore be used to measure the KAP of individuals with leprosy reactions in Indonesia. KAP questionnaires have the potential to identify gaps in understanding of leprosy reactions and are expected to be helpful in assessing the effectiveness of interventions.